Ghazali’s Juristic Treatment of the Shari‘ah Rules in al-Mustasfa (American Journal of Islam and Society, 1987)
IntroductionGhazali's approach to usul al-fiqh, as articulated in his last and greatestwork of Law, al-Mustasfa is based on the premise that, in essence, this scienceis knowledge of how to extract ahkam (rules) from the Shari'ah sources.(As for the science of fiqh, it concerns itself particularly with the Shari'ahrules themselves which have been established in order to qualify the acts ofthe locus of obligation, man.) Accordingly, Ghazali views it as imperativethat any discourse on usul focus on three essentail elements: the ahkam; theadilla (sources); and the means by which rules are extracted from these sources,which ultimately includes examination of the qualifications of the extractor,namely, the mujtahid. This paper lays out Ghazali's treatment in al-Mustasfaof the first of these elements, the ahkam.Hukm (The Shari’ah Address)Linguistically, hukm is the verbal noun of hakama, which signifies “withholding,restraint, prevention; and judgment, jurisdiction, rule, dominion,authority, or governinglq The technical meaning, however, varies accordingto its usages in the terminologies of philosophy, Arabic grammar, usul, and fiqh.Ghazali defines hukm as the Shan‘irh address ( khitab al-Shar’) in relationto the acts of the loci of obligation, the address being Allah’s revelationto His Messenger. It is divided into two categories: revelation for recitation(wahi matluww), that is, the Qur”an; and revelation not for recitation (wahighayr lww matu), namely, the Sunnah.